STATUS PEMANFAATAN SUMBERDAYA IKAN EKONOMIS PENTING DI SUNGAI-SUNGAI KAWASAN PANTAI TIMUR SUMATERA - Rudi Masuswo Purwoko; Kamaluddin Kasim; Husnah Husnah; Eko Prianto (Fakultas Perikanan dan Kelautan, Universitas Riau, 2020)
Inland general waters fish resources in the East coast of Sumatra are thought to have experienced more fishing pressure due to non-selective use of fishing gear. Changes in the size of fish caught are one of the main indicators of fishing pressure. This study aims to determine the status of economically important fish resource utilization in the rivers of the eastern coast of Sumatra, by estimating the spawning potential ratio (SPR). The research was conducted in the rivers of the East Coast region of Sumatra, including the Kampar, Batanghari and Musi Rivers from January to December 2016. The research method was through field surveys and collecting sample fish through fishermen and fish collectors. The types of fish collected were baung, lais, pond, siam sepat, cork, and betok. The results of the analysis of the SPR value in the Kampar River, where baung fish only amounted to 1%, 2% lais and 11% pond. In the Batanghari River, the SPR values reached 16% and 37% for siam sepat and cork fish, while in Musi River, the SPR value for siam sepat fish was 4%, baung and betok were 2% respectively. Overall this value is far below the recommended threshold value of SPR (30-40%). The rate of exploitation of fish resources is also high, it can be seen from the proportion of mortality due to fishing to natural mortality (F / M) of 2 to 6 times the natural mortality rate, which indicates the status of fish stocks in the wild is in an alarming condition.